(untitled) (Acta Scientiarum. Biological Sciences, 2021)
Some organisms, such as aquatic insects, are transported from the upstream to downstream region of streams through a process called drift. This process occurs in passive and active ways and can be variable throughout the day, mainly between the nocturnal and diurnal periods. Here, we evaluate the periodicity of the drift of aquatic insects in two streams of the Middle Iguaçu basin, southern region of Brazil. We predicted that the drift of aquatic insects brings the highest richness, diversity and abundance during the nocturnal period, compared to the diurnal period. In addition, we expected that the composition of species is different between these periods. In each stream, aquatic insect sampling was carried out 10 times, for 24 hours, using drift nets. A total of 2,114 aquatic insect specimens were recorded, distributed in 26 families. Of these families, 20 were recorded during the diurnal period and 24 during the nocturnal period. Our results showed an increase in the diversity and abundance of aquatic insect drift in the nocturnal period. However, only abundance was significantly different between the periods. We attribute the higher abundance in nocturnal drift possibly to biological interactions. Thus, nocturnal drift can be a strategy of some aquatic insects to avoid visual predation by other invertebrates and/or vertebrates, in Neotropical streams. We highlight the importance of our study, because it can be used for comparison in surveys of lotic environments that have been impacted by human activity (e.g. by dam construction), which can alter the water flow, and consequently the pattern of insect drift.